ENVIRONMENTAL SUSTAINABILITY ASSESSMENT OF SUGARCANE INDUSTRY USING LIFE CYCLE ASSESSMENT - Kautzar, Galuh Zuhria; Tama, Ishardita Pambudi; Sumantri, Yeni (JEMIS (Journal of Engineering & Management in Industrial System), 2020)
The sugarcane industry is one of the industries that generated negatives impact on the environment. Therefore, it can be concluded that the sugarcane industry is not environmentally sustainable. The results of this research show that the use of electricity from bagasse cogeneration becomes the main contributor to all of damage categories. Meanwhile, the highest contribution to damage categories is human health with a total score of 59%. The results of this research are expected to reduce the environmental impact produced by PT. X so that PT. X will be more environmentally sustainable.